Direct Radical Acetoxyphosphorylation of Styrenes Mediated by Manganese(III) - Zhou, Shao-Fang; Li, Da-Peng; Liu, Kui; Zou, Jian-Ping; Asekun, Olayinka Taiwo (Journal of organic chemistry, 2015)
Direct radical acetoxyphosphorylation of styrenes mediated by Mn(OAc)3 with diphenylphosphine oxide and dialkyl phosphites was described, and a new type of difunctionalization of alkenes was achieved.